Maize seed production communities in hills towards a new path of contract seed production in Nepal - KC, DB; Ferrara, GO; Gadal, N; Neupane, S; Puri, R; Khatiwada, B; Sharma, H (Agronomy Journal of Nepal, 2013)
Seed production of farmers preferred improved maize varieties under community based seed production(CBSP) group initiated in the hills of Nepal under Hill Maize Research Project in 2000. Trained members of the community group produce improved seeds identified through participatory varietal selection procedures. Despite quantum jump in maize seed production, 14 tons by 7 CBSP groups in 2000 to 1,036 tons by 207 groups in 2012, seed marketing remained one of the challenges in HMRP districts. Main objective of this study was to analyze maize seed production trend and presowing seed contracts in hill districts under HMRP. Linear regression model showed seed production trend over the period 2000 to 2012 highly significant. Annual compounded growth rate of seed during the same period was estimated to be 34.36%. Pre-sowing seed contract in cereal crops in the hills of Nepal is a new initiative of HMRP IV. Analysis showed 63 formal contracts were signed for 170.45 tons of improved maize seed between 50 CBSP groups and 24 private seed buyers/traders. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 150-155 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9017